The Impact of Task Interruptions on Audit Quality: Experimental Design in The Tunisian Audit Context - Ahmed Sallemi; Feten Arfaoui; Salma Damak Ayadi (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question - This study explores the impact of task interruptions on audit quality in Tunisia. Our research aimed to find out how Tunisian auditors felt about task interruptions and how they affected the quality of their assessment. Motivation - Our research question aims to clarify the perception of Tunisian auditors about interruptions and their impact on their judgments. This research highlights the position of Tunisian auditors on task interruptions and their impact on their quality of judgment. Idea - Its goal is to present several solutions for the auditors by creating a system where the bad interruptions are blocked to limit their impacts. Data - A triangulated study design was incorporated. Experimental and qualitative methods were used. Tools - We choose experimentation as a method of data collection to undertake hypothesis testing causal relationships. Findings - The results revealed that the interruptions of tasks do not affect the quality of judgment of the auditors in the Tunisian context. Furthermore, just the gender and length of work experience were included when evaluating the influence of various conditions. Contribution - Thus, this paper contributes to Tunisian audit research. Indeed, this study examines auditors' perceptions of task interruptions and their impact on their judgment quality. In addition, to attain the research's goal, this study relies on an experimental investigation and a qualitative confirmatory survey.
Keywords: M41; 650; Task interruptions -audit quality-Experimental design-Tunisian context